Prevalence of Hepatitis B virus among the physicians of Department of Medicine of Dhaka Medical College Hospital, Dhaka - Saha, Jayanto Kumar; Azad, Khan Abul Kalam; Hossain, Mohammad Zaid; Amin, Md Robed; Wazib, Amit; Rahman, Kazi Monisur (Journal of Dhaka Medical College, 2013)
Introduction: Hepatitis B virus is encountered sporadically throughout the year in Bangladesh. Bangladeshi physicians are also in a great risk for this blood-borne virus. To find out the seroprevalence of HBV and vaccination rate among the physicians, was the aim of this study. Methods: The study was an observational study and was conducted in the department of Medicine of Dhaka Medical College Hospital, Dhaka between April and September, 2012. Eighty physicians of department of Medicine were searched for hepatitis B virus with the help of a structured questionnaire. Physicians, who were found not vaccinated, were also investigated for HbsAg positivity by ELISA method. Results: Eighty five percent physicians were found vaccinated. Remaining 15% (12/80) physicians were investigated for HbsAg positivity but all were found negative. Vaccinated physicians who checked antibody titre (35.3%), were found well immunized. Fifty percent physicians experienced needle stick injury 2-5 times in their lifetime and 20% physicians did not use protective equipments during any invasive procedure. Conclusion: HBV remains a major cause of morbidity and mortality in Bangladesh. Hence, our physicians who were not vaccinated and also found HbsAg negative, should complete their vaccination schedule as early as possible. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15540 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 11-15